2021
DOI: 10.1007/s10853-021-05955-6
|View full text |Cite
|
Sign up to set email alerts
|

In- and out-plane transport properties of chemical vapor deposited TiO2 anatase films

Abstract: Due to their polymorphism, TiO2 films are quintessential components of state-of-the-art functional materials and devices for various applications from Dynamic Random Access Memory to Solar Water Splitting. However, contrary to other semiconductor/dielectric materials, the relationship between structural/morphological and electrical properties at the nano and micro scales remains unclear. In this context, the morphological characteristics of TiO2 films obtained by Metal-Organic Chemical Vapor Deposition (MOCVD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
(75 reference statements)
1
7
0
Order By: Relevance
“…These observations are in agreement with the literature: it was previously reported that the deposition temperature (475 • C) is in the range that favours the columnar growth of the coating [59]. The grains seen in Figure 2a-e are, therefore, the heads of the columns.…”
Section: Characterisation Of Tio 2 Coatingssupporting
confidence: 93%
“…These observations are in agreement with the literature: it was previously reported that the deposition temperature (475 • C) is in the range that favours the columnar growth of the coating [59]. The grains seen in Figure 2a-e are, therefore, the heads of the columns.…”
Section: Characterisation Of Tio 2 Coatingssupporting
confidence: 93%
“…Over the past years, researchers in the major of water treatment have focused on the improvement of nano materials which act as photocatalysts [16][17][18][19][20][21][22][23][24][25][26][27]. Several semiconductors such as SnO2, WO3,TiO2, CeO2, and ZnO have been utilized as heterogeneous photocatalysis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale electrical characterizations were carried out on a Bruker Multimode 8 setup using three different modes: Electrostatic Force Microscopy (EFM) for the dielectric permittivity [29,30], Kelvin Probe Force Microscopy (KPFM) for the charge injection and trapping dynamics [31] and the Conductive AFM (C-AFM) for the current flowing through the NC films [32]. Experimental setups are described in figure 1.…”
Section: Nanoscale Electrical Characterizationsmentioning
confidence: 99%